Independensi Beritatrends.Com dalam Pemberitaan Politik Lokal Jawa Timur - Asna Istya Marwantika; Nurwahyuni Nurwahyuni (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2021)
This article reviews east Java's local political news on the online news portal Beritatrends.com, a news portal based in the Magetan region of East Java. The focus of the issue under review is how the editorial process in the production of local political news editions in February-October 2018, and how the independence of local political news editions in february-October 2018 editions in online media Beritatrends.com. The analysis used in this article is a content analysis technique. The results of the analysis showed that the editorial process in the production of online media Beritatrends.com has been in accordance with the standards and stages of the procedure of the news production process which includes pre-production, production, and post-production. Local political news in the Beritatrends.com February-October 2018, appeared independent. News content contains personalized elements in a particular person, so that the reader is directed to positive opinions and stereotypes to an object. Although the appearance of some local political news Beritatrends.com is not independent, but the news is presented by fulfilling the elements of good news, namely the presence of elements 5W + 1H, and the news is accurate by listing the time of an event, the suitability of the news headline with the content of the news, including photos or images of events as supporting data.